LAW NUMBER 6 YEAR 2014 ABOUT VILLAGE REGULATION AS A LEX SPECIALIST IN INDONESIAN NATIONAL LAW POLITICS - Ghannesdeva Nadia Yossita (Fakultas Hukum Universitas Kadiri, 2021)
Abstractvillages, since the enactment of Law Number 6 of 2014 concerning Villages, are gettingstronger and exist as autonomous regions with the authority to regulate and managetheir own affairs even down to budget and welfare matters. The law clearly statesvillage regulations as statutory regulations stipulated by the Village Head after beingdiscussed and agreed upon with the Village Consultative Body. This can be thought ofas a small constitution where the Village looks like a small state that has its owngovernment, they are ready with a village head who carries out the rules and has thecharacter of an executive and also a deliberative council that looks like a villageparliament that enforces these regulations and it is like a legislative body. This can leadto legal uncertainty because of the many interpretations, especially the interpretation ofArticle 8 of Law Number 12 Year 2011 regarding the status, position and existence ofVillage Regulations in the hierarchy of statutory regulations in Indonesia. Furthermore,it has an impact on village government, namely the existence of legal uncertainty, onthe one hand to carry out the wheels of government, the village government must havea legal basis, namely village regulations, but on the other hand, village regulations areno longer listed in the hierarchy of State statutory regulations.Key words : Village Law, Legal Number 06 year 2014, Village political